Analisis Peningkatan Kinerja Dosen melalui Implementasi Corporate Social Responsibility Internal di Universitas Muhammadiyah Ponorogo - Adi Santoso (Jurnal Maksipreneur, 2018)
This research aims to examine and analyze the effect of disclosure of Internal Corporate Social Responsibility (CSR) with dimensions of diversity (X1) and employee support (X2) against the performance of a lecturer (Y) at the University of Muhammadiyah Ponorogo. The population in this research is the entire existing lecturer in University of Muhammadiyah Ponorogo totalling 187 people using proportional stratified further allocated by random sampling techniques. The taking of the sample uses the Slovin's formula with a defined precision of 5% found the total number of respondents as a sample research as much a withdrawal of samples of research done using proportional stratified random sampling found the number of research sample as much as 120 respondents. The results of this study found that internal CSR dimension i.e. diversity and employee support a positive and significant effect against lecturers’ performance improvements in the scope of the University of Muhammadiyah Ponorogo. So it can be inferred that the work environment at the University of Muhammadiyah Ponorogo relating to diversity, there is no element of intimidation with regard to issues of gender, race, tribe, and religion so that it is managed to encourage lecturers to improve its performance. Similarly, the disclosure of the internal dimension of CSR employee support felt very motivating lecturers to enhance the quality of work and professionalism of lecturers, although one of the indicator of employee support i.e. administering payroll subject matter has not too fulfilling for lecturers.